3ab-2b=3a-b

Simple and best practice solution for 3ab-2b=3a-b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3ab-2b=3a-b equation:


Simplifying
3ab + -2b = 3a + -1b

Solving
3ab + -2b = 3a + -1b

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-3a' to each side of the equation.
3ab + -3a + -2b = 3a + -3a + -1b

Reorder the terms:
-3a + 3ab + -2b = 3a + -3a + -1b

Combine like terms: 3a + -3a = 0
-3a + 3ab + -2b = 0 + -1b
-3a + 3ab + -2b = -1b

Add '2b' to each side of the equation.
-3a + 3ab + -2b + 2b = -1b + 2b

Combine like terms: -2b + 2b = 0
-3a + 3ab + 0 = -1b + 2b
-3a + 3ab = -1b + 2b

Combine like terms: -1b + 2b = 1b
-3a + 3ab = 1b

Combine like terms: 1b + -1b = 0
-3a + 3ab + -1b = 0

The solution to this equation could not be determined.

See similar equations:

| -3x^2-3x+90=0 | | 1.2y-0.3x=0.12 | | -7x-5y=11 | | X/11=-22 | | f(x)=2x^2-16x+27 | | 3Y-9-3Y=-9 | | 1.2x-0.3y=0.12 | | 12-7x=9x-5x-87 | | 4x^3+72x^2+68x=0 | | 5/6-x/6=6/5 | | 2^3*x=1/64 | | 3x-5x+4-x+7=88 | | -3x+8=5x-2 | | -x^3+10x^2+39x=0 | | 3x-7=3(x-3)+3 | | ln(x+5)=ln(x-4)-ln(x+4) | | a-1/2=2a-2/3 | | 4x+15x+6=3x-14 | | 19+20m+m^2= | | 24x+8x^2+2x^3=0 | | .4w-.3w+.4w=3 | | 3(2x-5)=5(x-4+x) | | 9c^3+12c^2=0 | | 4x^3-48x^2+140x=0 | | 100/10= | | 5(7x+1)=320 | | 3x+2x+3+5x-13=180 | | 2c+4d=8 | | 45m-90=90m | | P=5s-(100-2s) | | -3(y+5)y=6 | | 6(9+4x)=222 |

Equations solver categories